Do Changes in Hemodynamic Parameters Depend Upon Length of Sleep Deprivation? Comparison Between Subjects With Normal Blood Pressure, Prehypertension, and Hypertension - Słomko, Joanna; Zawadka-Kunikowska, Monika; Kujawski, Sławomir; Klawe, Jacek J.; Tafil-Klawe, Małgorzata; Newton, Julia L.; Zalewski, Paweł (Frontiers in Physiology, 2018)
The main objective of the study was to analyze the impact of sleep deprivation upon hemodynamic and autonomic parameters in subjects with normal blood pressure compared to prehypertension and hypertension at 24, 28 and 32 hours of total sleep deprivation (TSD). Thirty volunteers, healthy men with current medical tests indicating the absence of disease took part in the study. After physical examination (basic neurological, clinical examination, echocardiography and doppler ultrasound of the renal arteries, evaluation of the autonomic nervous system) subjects were divided into 3 groups: I – normotensive, II – pre-hypertensive, III – hypertensive (age: 31.2±2.1 vs 33.5±2.7 vs 36.8±2.7 years, p>0.05; BMI: 25.2±0.8 vs 29.0±1.5 vs 26.4±1.0 kg/m2, p>0.05). Hemodynamic and autonomic parameters were automatically measured at rest and in a tilted position with a Task Force Monitor. The Task Force Monitor consists of electrocardiography, impedance cardiography, oscillometric and continuous blood pressure measurement. Mixed models with random effects was applied in order to analyze the parameters’ dependence on the time and the group of patients. One-way ANOVA or Kruskal Wallis test were used to detect differences between groups in each time point. In the pre-hypertensive group 28-h TSD resulted in increased vagal outflow (changes in high frequency heart rate variability, p=0.0189), as evidenced by decreased heart rate (p=0.0293). Moreover after 24-h TSD and 28-h TSD we observed changes in blood pressure parameters. In hypertensive group the most important changes in hemodynamic parameters: systolic blood pressure (sBP, p=0.0031), diastolic blood pressure (dBP, p=0.0136), cardiac output (CO, p=0.0439) and changes in heart rate (HR, p=0.0063) after tilt test were observed after 32-h TSD. In conclusion, our results show that changes in hemodynamic parameters during sleep deprivation depend on the baseline blood pressure and duration of TSD. What is important, both groups reported a decrease of sBP and dBP during the TSD (pre-hypertensive group after 24, 28-h TSD; hypertensive group after 32-h TSD. In our opinion this is the first study which considers three homogenous groups in terms of gender: only men, during different points of acute TSD: 24, 28 and 32 hours of TSD in laboratory condition.